Formation Mechanism of Mud Volcanoes/Mud Diapirs Based on Physical Simulation - Zhifeng Wan; Jinfeng Zhang; Guoqing Lin; Siling Zhong; Qing Li; Jiangong Wei; Yuefeng Sun (Geofluids)
The formation of mud volcanoes/mud diapirs is directly related to oil and gas accumulation and gas-hydrate mineralization. Their eruptive activities easily cause engineering accidents and may increase the greenhouse effect by the eruption of methane gas. Many scholars have performed much research on the developmental characteristics, geochemistry, and carbon emissions of mud diapirs/mud volcanoes, but the formation mechanism of mud diapirs/mud volcanoes is still controversial. Mud diapirs and mud volcanoes are especially developed in the northern South China Sea and are accompanied by abundant oil, gas, and gas-hydrate resources. Based on the mud volcanoes/mud diapirs in the northern South China Sea, the physical simulation experiments of mud diapir/mud volcano formation and evolution under different fluid pressures and tectonic environments have been performed by loading a fluid-input system in traditional sandbox simulation equipment. The genetic mechanism of mud diapirs/mud volcanoes is revealed, and a fluid-leakage model of mud diapirs/mud volcanoes under different geological conditions is established. We believe that in an overpressured environment, the greater the thickness of the overlying strata is, the greater the pressure or power required for the upward migration of muddy fluid to penetrate the overlying strata. Tectonic activity promotes the development of mud volcanos/mud diapirs. To a certain extent, the more intense the tectonic activity is, the more significant the effect of promoting the development of mud volcanoes/mud diapirs and the larger the mud diapirs/mud volcanoes become.